The Relationship Between Parents Verbal Communication Toward Children's Language Brightness at Kindergarden State 1 Padang City - Sahriana Desi Rambe; Elise Muryanti (Program Studi PGRA, 2019)
The purpose of this study was to see how the relationship of parents' verbal communication to children's language politeness in Taman Kanak-Kanak (Public kindergarten) 1 Padang. This research is a type of collaborative research using quantitative methods that involve data collection in the form of questionnaires. And data processing using SPSS program version 21. Based on data analysis obtained the coefficient of determination of verbal communication of parents to the politeness of children's language by 0.294, the correlation coefficient between the relationship of verbal communication of parents to the politeness of children's language by 0.241. This means that parents' verbal communication of 49.1% of the child's politeness is significant at the 5% level.